2014
DOI: 10.1111/epi.12531
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of diagnosis and therapeutic care of epilepsy at a tertiary referral center in Nigeria

Abstract: SUMMARYObjective: Epilepsy care in developing countries is challenged by the paucity of trained specialists, diagnostic tools, and antiepileptic drugs (AEDs). We retrospectively evaluated how epilepsy was managed in a Nigerian tertiary referral center, with the goals of determining diagnostic accuracy by comparing clinical and electroencephalography (EEG) diagnoses, the appropriateness of prescribed therapy by clinician specialization, and the association between therapy and patient outcomes. Methods: We exami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
7
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(19 citation statements)
references
References 15 publications
9
7
3
Order By: Relevance
“…The mean age of our patients was 18.55 years, demonstrating the young age of the majority of patients in the study sample. The study also showed a predominance of the male sex (sex ratio at 1.5), as previously reported in many studies in sub‐Saharan Africa . However, the predominance of female sex has been reported in some studies in Nigeria, Rwanda, and Tanzanie .…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…The mean age of our patients was 18.55 years, demonstrating the young age of the majority of patients in the study sample. The study also showed a predominance of the male sex (sex ratio at 1.5), as previously reported in many studies in sub‐Saharan Africa . However, the predominance of female sex has been reported in some studies in Nigeria, Rwanda, and Tanzanie .…”
Section: Discussionsupporting
confidence: 88%
“…A study from Togo reported a high proportion of patients with infectious and structural etiologies (69.4%) . A Nigerian study reported a proportion of idiopathic generalized epilepsies of 17.1% . Despite the means to carry out additional examinations (such as laboratory tests, brain CT scan, or/and MRI), which is not always possible in studies conducted in some sub‐Saharan African countries, we found a high proportion of idiopathic generalized epilepsies in our study than those so far reported.…”
Section: Discussioncontrasting
confidence: 83%
See 3 more Smart Citations